The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/jfpp.13571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electrical stimulation applied in combination with shock chilling method on selected quality attributes of beef from young bulls, heifers, and cows carcasses

Abstract: The study was aimed at determining the effect of electrical stimulation (ES) and shock method of chilling on beef pH, tenderness and losses of half‐carcass weight. It was demonstrated that the use of treatments caused a rapid acceleration of the post mortem changes rate in heifers and cows half‐carcasses meat. ES accelerated pH decline in bulls half‐carcasses as well, however did not cause the differences in the ultimate pH. The treatments allowed to obtain 90 and 70% of heifers and cows half‐carcasses, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The subsequent part of the study aimed to determine the effect of different meat production variants (chilling method slow, fast, accelerated + ES/NES) on changes in the industrial indicators (pH and temperature) of beef quality [ 32 , 38 ]. This complex approach was expected to allow identifying the optimal variant of meat production, ensure its high quality, and reduce its harmful effect on environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The subsequent part of the study aimed to determine the effect of different meat production variants (chilling method slow, fast, accelerated + ES/NES) on changes in the industrial indicators (pH and temperature) of beef quality [ 32 , 38 ]. This complex approach was expected to allow identifying the optimal variant of meat production, ensure its high quality, and reduce its harmful effect on environment.…”
Section: Resultsmentioning
confidence: 99%
“…Given the results presented above, it has been concluded that the coupled use of HEVS performed using an own-construction device and a fast chilling method is justified considering both the economic and meat quality class established based on pH [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the possibility of exciting muscles through both the nervous system and muscle fiber conductivity, the HVES is considered the most effective method for meat quality improvement (Żywica, 2010). For this reason, the second part of this study aimed to determine the effect of high-voltage electrical stimulation of beef half-carcasses with an own-construction device (Żywica & Banach 2014) and their chilling with three methods: slow, accelerated, and fast two-phase, on the rate of changes in meat pH, being its main quality attribute (Contreras-Castillo et al 2016; Banach et al 2018). This complex approach was expected to allow identifying the optimal variant of meat production, ensure its high quality and reduce its harmful effect on environment.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies held to the principle of –1 °C by 5 hr postmortem, such as chilling beef loins at –20 °C so the temperature reached –1.5 °C within 1.5 hr (Table , F1, F2), or allowing beef loins chilled at –20 °C to reach 0 °C at 2 hr postmortem (Table , F4). Some blast chilling procedures have also been studied, where beef muscles were held at –30 to –40 °C until the core temperature reached –1 °C at 3.5 hr postmortem (Table , F13), or shock chilling, where carcass sides were chilled at –3 to –5 °C until the freezing point was reached on the surface of the carcass (Banach, Modzelewska‐Kapituła, Wichman, Tkacz, & Żywica, ; Troeger, ; Żywica, Banach, & Gornowicz, ); or cryogenic chilling, where beef carcasses were held at –70 °C for 5 hr, and then the carcasses reached –2 to 0 °C at 5 hr postmortem (Table , F20). In lamb, the very fast chilling has been evaluated, where loins were chilled at –15 °C and the temperature of the muscle reached –1.9 to 0.7 °C (Table , F22 to F25); and ultra‐rapid chilling in which suckling lamb carcasses were chilled at –20 °C for 3.5 hr, and the temperature at 5 hr was –0.1 °C (Table , F31 to F32).…”
Section: Overview Of the Chilling Methods Applied To Red Meatmentioning
confidence: 99%